Pengaruh Store Image Toko Ikan Hias Terhadap Keputusan Pembelian Konsumen - Indah Handaruwati (Jurnal Inovasi Bisnis dan Kewirausahaan, 2021)
This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table.V This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is smaller than t table. Price affects consumer purchasing decisions at the Bintang Aquarium Solo shop, as evidenced by the t value of 2,400, while the significance value is 0.018, so the value of t is greater than the value of t table. This study aims to analyze the effect of the store image of an ornamental fish shop which consists of merchandise variables, shop location, employee services, and prices on consumer purchasing decisions. The sample in this study were 105 respondents who were willing and willing to take the time to fill out a questionnaire that was taken using purposive and convience sampling methods. Data collection using a questionnaire. Data analysis was performed by multiple linear regression with SPSS 17.00 software. The results of this study indicate that merchandise has an effect on consumer purchasing decisions with a significance value of 0.002, while the t table is 3.260, so the value of t count is greater than the t table. Store location does not have a significant effect on purchasing decisions at the Bintang Aquarium Solo Shop, as evidenced by a significance value of 0.551 while t count 0.598, the t value is smaller than the t table value. Employee service is not significant towards consumer purchasing decisions at Bintang Aquarium Solo Shop, as evidenced by the t value of 1.450 while the significance value is 0.150, so the value of t count is small